CHALLENGES TO BUILDING SUSTAINABILITY; CASE STUDY OF GREEN BUILDING IMPLEMENTATION IN ABUBAKAR TAFAWA BALEWA UNIVERSITY BAUCHI, NIGERIA - Milala, Sani Inusa; Danladi, Audu; Manga, Shuaibu H.; Ibrahim, Inusa (UI Scholars Hub, 2022)
Abubakar Tafawa Balewa University (ATBU) has become the tip of the iceberg since technology globalization has created a welcoming environment for green construction. However, there are several roadblocks to overcome, this includes barriers to technology. Dependence on technology stifles the autonomous growth of one's technology. This implementation of sustainable green building has been implemented in ATBU such as green construction, financing, among others. The study has the primary aim of assessing the impediment to the sustainable implementation of green building practices in ATBU. Quantitative research design is adopted in this study where questionnaire survey strategy was used to collect data. There is a total of 180 staff that constitute the respondent scope where Krejcie and Morgan table of 1970 are used to determine the sample. 123 are adopted as a sample. In the process of the survey, 123 survey are distributed and only 101 are retrieved for the descriptive analysis and correlational statistical analysis was used in the exploration of the result. It was found that good ventilation light is the indicator of the green building that was lacking a technical know-how, with lack of professionals to handle the task, and the predominant practice by governments and institutions of separating capital and operating budgets rather than applying life-cycle budgeting. The study found .650** strong correlational relationship between green building and performance of academic activities. The study concluded that there is a low level of green building awareness in Abubakar Tafawa Balewa University Bauchi. The building projects in Abubakar Tafawa Balewa University Bauchi adopted few elements of green building assessment categories and the level of green building practice of Abubakar Tafawa Balewa University Bauchi building projects to each building assessment categories is not in line with the green building practice. This study will further enable the environment of the abubakar tafawa balewa university to consider various options by using this study as a benchmark for the evaluation and ranking among the global university.